2002
DOI: 10.1046/j.1365-2249.2002.01868.x
|View full text |Cite
|
Sign up to set email alerts
|

Simultaneous analysis of T cell clonality and cytokine production in rheumatoid arthritis using three-colour flow cytometry

Abstract: SUMMARY In this study we examined the cytokine production by T cells and TCRVβ subsets in peripheral blood (PB) and synovial fluid (SF) from six RA patients and PB from 10 normal subjects, using three‐colour flow cytometry. In two RA subjects we assessed T cell clonality by RT PCR using TCRBV family‐specific primers and analysed the CDR3 (complementarity determining region 3) length by GeneScan analysis. A high percentage of IFN‐γ‐ and IL‐2‐ producing cells was observed among the PB T cells in both the RA pati… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

1
6
0

Year Published

2005
2005
2016
2016

Publication Types

Select...
4
2
1

Relationship

0
7

Authors

Journals

citations
Cited by 10 publications
(7 citation statements)
references
References 55 publications
(44 reference statements)
1
6
0
Order By: Relevance
“…Several lines of evidence suggest that T cells play an important role in the pathogenesis of RA and MS. A skewed TCR repertoire was observed in RA patients, but none of the Vβ genes was found to be consistently overexpressed in all, or a subgroup, of RA patients. 2,4,19 Although several putative autoantigens have been implicated as candidate antigens in RA (collagen, proteoglycans, heat-shock proteins [HSPs]) and MS (myelin components), the "disease-triggering" antigen (or antigens) has not been identified. 20 These findings support the concept that autoimmune diseases are not caused by a single autoantigen, but rather result from a general dysfunction of peripheral immune system tolerance or homeostasis mechanisms.…”
Section: Discussionmentioning
confidence: 99%
See 2 more Smart Citations
“…Several lines of evidence suggest that T cells play an important role in the pathogenesis of RA and MS. A skewed TCR repertoire was observed in RA patients, but none of the Vβ genes was found to be consistently overexpressed in all, or a subgroup, of RA patients. 2,4,19 Although several putative autoantigens have been implicated as candidate antigens in RA (collagen, proteoglycans, heat-shock proteins [HSPs]) and MS (myelin components), the "disease-triggering" antigen (or antigens) has not been identified. 20 These findings support the concept that autoimmune diseases are not caused by a single autoantigen, but rather result from a general dysfunction of peripheral immune system tolerance or homeostasis mechanisms.…”
Section: Discussionmentioning
confidence: 99%
“…Patients with T‐cell‐ mediated AIDs show immune system abnormalities that resemble the typical characteristics of immune dysfunction described in the elderly. Several research groups have observed T‐cell clonal expansions in the peripheral blood of rheumatoid arthritis (RA) patients 1‐4. Others have reported a population of T cells in RA patients with signs of replicative stress 2‐6.…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation
“…With increasing disease duration a number of phenotypic and functional T cell defects have been described in RA including hyporesponsiveness of T cells to stimulation, a decline in naive CD4+ T cells and a disturbance in the naive T cell receptor (TCR) repertoire indicated by a loss of TCR diversity and clonal expansion of a proportion of T cells [3][4][5]. The capacity of lymphocytes to clonally expand may be mediated, at least in part, through the upregulation of telomerase.…”
Section: Introductionmentioning
confidence: 99%
“…However, this mechanism induces replicative stress on peripheral T cells. Several research groups have observed T cell clonal expansions in the peripheral blood of RA patients (7–10) and have reported a population of T cells with signs of replicative stress in RA patients (8–12). Replicatively stressed cells have lost the expression of the major costimulatory molecule CD28, accompanied by phenotypic and functional changes (13).…”
mentioning
confidence: 99%